Faktor Makro Ekonomi Yang Mempengaruhi Pergerakan Harga Saham Pada Indeks Saham Syariah Indonesia (ISSI) di Bursa Efek Indonesia (BEI) - Rachmawati, Martien; Laila, Nisful (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The capital market presence is such an important concern for many country because it relate to its function as economic booster through investation. This study aims to analyze macro economic factors that can affect the movement of stock price at Indonesia Sharia Stock Index in Indonesia Stock Exchange as the inflation factor, SBI interest rates and exchange rates. The method used in this research is quantitative approaches in which data is obtained from Indonesia Stock Exchange and Bank of Indonesia. The data used is the time series data starting from January 2012 to April 2015. The statistical tool used is multiple linear regression. Result showed that partially inflation is not significant and have a negative relation toward ISSI's stock price, SBI interest rate is not significant and have a positive relation toward ISSI's stock price, exchange rate significantly influence the stock price at Indonesia Sharia Stock Index (ISSI) and have a negative effect. Simultaneously, both variable inflation rate, SBI interest rate and the exchange rate significantly influence the stock price's movement at Indonesia Sharia Stock Index (ISSI).